INSPIRASI ATT (ALAT TRANSPORTASI TRADISIONAL) SEBAGAI MOTIF KAIN BATIK - Noor Sudiyati; Sunarto Sunarto; Made Sukanadi; Pandansari Kusumo (Institut Seni Indonesia Yogyakarta, 2016)
Historically, traditional transport is very interesting to be analyzed. The people ofYogyakarta has had various traditional transport as the artifact with different meanings. Decadesago, the traditional horse cart (andong), cart, and classic cart currently kept in the Royal Museumas well as cow cart were the reliable transport for public mobility. Other vehicles were traditionalpedicab (becak) and bicycles both for male and female riders.The artifacts have currently not been in operation any longer. Although some peoplehave attempted to reserve the existence of those traditional transport, such as the cow cartcommunity, traditional bicycle community, and still many others, the reservation has to be takenmore seriously in order that the young generation have the sense of belonging. They have to beproud of the fact that the ancestors already had such traditional transports.The data concerning the traditional transports was collected from the regions inYogyakarta which still reserve the artifacts. Only few are operated, while most of them arereserved in such museums as the Royal Museum of Yogyakarta. The ancient Royal Palace usedto operate their classic carts for royal events. The carts had different functions, performances,and esthetics. They also symbolize different historical meanings. The parts of the carts have highesthetic value and craftsmanship. The decoration is sophisticated and can be transformed intovisualized works for further reservation.To reserve the historical artifacts and parts with their artistic value, they are put into themotif of batik in Yogyakarta. In this way, batik Yogyakarta will be have richer motifs. Such motifsand patterns as the traditional transports as becak and bicycle are reserved on batik. It isexpected that the young generation will proudly see and appreciate the wonderful historicalvalue inherited by the ancestors.Key Words: Traditional Transport, history, reserve, inspiration, Batik motif Garis kesejarahan akan Angkutan Tradisional menarik untuk dikaji, MasyarakatYogyakarta memiliki sejarah Angkutan Tradisional sebagai kekayaan artefak peninggalan, yangmenyiratkan berbagai makna. ATT: Andhong, kereta , kereta klasik yang ada di Museum Keretakeraoin, serta gerobag sapi itu puluhan tahun yang lalu menjadi andalan bagi mobilitasmasyarakat kita. Dilengkapi dengan becak dan sepeda onthel lanang maupun wedhok. KiniArtefak tersebut tinggal kenangan. Walaupun masih ada yang nguri-uri sebagaimana berdirikomunitas gerobag sapi, komunitas sepeda onthel dan yang lain, namun perlu dilestarikan untuk kepentingan generasi muda agar masih memiliki rasa handarbeni: bahwa dulu leluhurnyamemiliki berjenis-jenis kendaraan tradisional.Upaya untuk mendapatkan data dari ATTT didapatkan di daerah Yogyakarta yang masihartefak dan masih aktif dijalankan, sebagian besar sudah dilestarikan dalam museum sepertimuseum kereta di Keraton Yogyakarta. Kereta klasik yang pernah dimiliki kerajaan Yogyakartatersebut bermacam fungsi, performent dan estetikanya. Semua itu bermakna, sebagai buktisejarah Keberadaan Angkutan Transfortasi Tradisional. Artefak tranportasi itu memiliki bagianbagianyang estetis, bernilai craft yang tinggi, penuh hiasan yang rumit, semuanya menjadiobyek estetika yang dapat dilanjutkan lagi menjadi karya-karya visual yang dapat memberikannilai kelestarian.Untuk melestarikan artefak bersejarah dan bagian-bagian yang memiliki nilai artistictersebut, selaras apabila dijadikan inspirasi sebagai motif batik bagi Yogyakarta, agar menambahbarisan panjang motif yang dimiliki oleh dunia perbatikan kota Yogyakarta, ATT seperti becak,sepeda tersebut diangkat menjadi inspirasi untuk pola dan motif batik. Agar lestari dan generasidapat menyaksikan dan tidak kehilangan nilai sejarah yang dimiliki para pendahulu. Kata kunci: alat transportasi tradisional, sejarah, melestarikan, inspirasi, motif, batik.